Determination the concentration for uranium in phosphrous fertilizers by using nuclear track detector CR-39 (Baghdad Science Journal, 2025)
The aim of this research was to study the concentrations of Uranium in the phosphorus fertilizers using Nuclear track detector (CR-39).Our present investigation is based on the study of 10 types samples for different kinds of phosphorus fertilizers which were available in the local market Some of them were Iraqi made and the others from different countries like, (Iran, Italy, Holland, Lebanon and Jordan) ..The result obtained shows that the Uranium concentration in phosphorus fertilizers samples varies from (3.59ppm) to(2.59ppm). Based on the radioactive concentration of Uranium in the samples all the results obtained between(3.59ppm) in the Iraqi super phosphate to (2.59ppm) in the mixture Iraqi phosphate fertilizer are within the international levels as given by IAEA (International atomic Energy Agency) date if compares that equal by 12ppm .